2024
DOI: 10.3345/cep.2023.00486
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety, depression, and stress among parents of neonates admitted to neonatal intensive care unit: a systematic review and meta-analysis

Asha P. Shetty,
Kurvatteppa Halemani,
Alwin Issac
et al.

Abstract: Background: Neonatal intensive care unit (NICU) admission causes significant distress that can hinder the successful transition into parenthood, child-parent relations, and child development.Purpose: This systematic review and meta-analysis aimed to understand parental psychological phenomena. Here we assessed the emotional response of parents of newborns during NICU admission.Methods: Two authors independently searched the PubMed, Cumulative Index to Nursing and Allied Health Literature, Embase, Clinical Key,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These prevalences are in line with Shetty et al systematic review that found in the NICU setting a pooled prevalence of stress of 41% among mothers versus 22% in fathers. 13 When looking at depression and anxiety, results of our study showed that both conditions were more frequent in mothers, though significantly so for depression and trait anxiety. These results are to a large extent aligned with previous studies, although again literature is not fully consistent.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…These prevalences are in line with Shetty et al systematic review that found in the NICU setting a pooled prevalence of stress of 41% among mothers versus 22% in fathers. 13 When looking at depression and anxiety, results of our study showed that both conditions were more frequent in mothers, though significantly so for depression and trait anxiety. These results are to a large extent aligned with previous studies, although again literature is not fully consistent.…”
Section: Discussionmentioning
confidence: 54%
“…In line with our study, a recent systematic review found that in the NICU setting, the pooled prevalence of stress, anxiety and depression is significantly higher among mothers than fathers. 13 Overall, our findings suggest that more attention should be given to the mental health of parents of infants hospitalised in the NICU, particularly to mothers, who are more directly involved in newborn care. This includes the need for more studies, to better describe differences in mental health indicators and participation in care among mothers and fathers in different settings and to describe tailored interventions, both in support of parents and staff.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations